Cultural Diversity, Ethnocentrism and Terrorism in Mukoma WA Ngugi’s Black Star Nairobi (2013) - Babacar Diakhaté (Britain International for Academic Research (BIAR) Publisher, 2020)
This article brings to light the obstacles that impede countries like Kenya to develop. In Black Star Nairobi, Mukoma WA Ngugi addresses cultural diversity issues and ethnic crisis. Like other African writers such as Chinua Achebe, Ngugi WA Thiong’o, Chimamanda Ngozi Adichie, Mukoma WA Ngugi displays to what extent Kenyans are tied to their cultures, traditions and ethnics. He demonstrates how ethnocentrism can have an impact on the socio-political activities of his people. He also pinpoints the drawbacks engendered by ethnocentrism like radicalization, terrorism and illegal immigration.